Neowaskularyzacja podsiatkówkowa udzieci – występowanie, diagnostyka, leczenie - Bernardczyk-Meller, Jadwiga; Kłosowska-Zawadka, Anna; Wasiewicz-Rager, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Choroidal neovascularization (CNV) belongs to the rare retinal disorders in children. Authors present 3 cases of CNV, which were diagnosed in patients between 12-15 years of age (2 females and 1 male). Complete ophthalmological examination including fluorescein angiography, indocyanin angiography and optical coherence tomography were performed in all cases. Laboratory tests to exclude the systemic diseases were also done. CNV in young people maybe a result of high myopia, angioid streaks, ocular histoplasmosis, trauma or it could be idiopatic. In our series, we found idiopatic CNV in 2 eyes and 1 CNV after traumatic choroidal break. Stabilization of visual acuity was achieved after argon laser treatment in 2 cases.